Hybrid Physical Education Teaching Process in Colleges: A Performance Evaluation Perspective Using the Single Valued Bipolar Pentapartitioned Neutrosophic Set - Guifang Shen (Neutrosophic Sets and Systems)
A major shift in pedagogical techniques is represented by the incorporation of hybrid teaching models into college-level physical education (PE), particularly in response to the demand for flexible learning settings and technology innovation. By creating a multifaceted framework that includes instructional clarity, student involvement, technology accessibility, physical fitness outcomes, and overall satisfaction, this study investigates the performance evaluation of hybrid physical education programs. Six hybrid models were evaluated for their ability to improve educational results using both qualitative and quantitative criteria. This study uses the Single Valued Bipolar Pentapartitioned Neutrosophic Set to overcome uncertainty information. The results show that, when backed by capable training and easily available digital infrastructure, well-designed hybrid systems may greatly increase learning flexibility, enhance physical health, and foster greater student autonomy. For institutions looking to maximize the hybrid PE experience and guarantee sustainable performance requirements, the report offers evidence-based recommendations.